SLAVIC GODDESS MOKOSHA: LINGUOCULTURAL DIMENSION - Циганок, О.; Санівський, О. (Modern engineering and innovative technologies, 2023)
The paper examines the linguistic and cultural dimension of the image of the Slavic goddess Mokoshi. Historical and literary sources were analyzed, the etymology of the name Mokosha was clarified on the basis of encyclopedic, literary, mythological and fo